A Path Forward in Nurse-Led Research: Turning Priorities Into Actionable Items. (May 2023) - Cámpoli, Marcela; Mulvey, Tanya
Abstract : To raise nurses' voices and promote nurse-led research, the American Nurses Credentialing Center's Research Council 2022 Research Priorities included disseminating a research agenda for practice-based research, promoting interprofessional research, and encouraging equitable and inclusive participation on research teams. Expressions of nurses from around the world, however, described how organizational constraints and financial barriers are real challenges that nurse researchers must face, along with forming interdisciplinary teams to work with human subjects. Entities doing research seem to have a heavy focus on academic research where clinical bedside nurses feel separated from nursing research. Including all frontline nurses in research is a must; therefore, nurses' voices are loud and clear when asking for global efforts to be reoriented toward nurse-led, practice-based research and to turn the research priorities into easy-to-carry-forward and achievable actionable items.